The Positive Airway Pressure Therapy Compliance In Mild OSAS - Sezgi Şahin Duyar; Deniz Çelik; Funda Aksu; Selma Fırat (Turkish Journal of Internal Medicine, 2022)
Introduction: This study is designed to determine the factors for predicting the PAP compliance in mild obstructive sleep apnea syndrome (OSAS) for improving the cost-effectiveness in the treatment choices of these patients. Method: The study group comprises 27 mild OSAS patients who underwent automatic positive airway pressure (APAP) titration between July 2016 and December 2017. Demographic, clinic and polysomnographic characteristics of the patients were retrospectively evaluated. Compliance with PAP treatment was defined as the usage of 5 nights/week and 4 hours/night at least. Data of compliant patients were statistically compared with non-compliant patients. Results: Most of the patients (23 patients, 85,2%) were prescribed APAP devices. Acceptable compliance at the end of the first year of therapy was achieved by 11 patients (40,2%) whereas 8 patients used PAP device 2 months at most (29,6%) The remaining 8 patients had not taken the device at all and were considered as non-adherent to PAP treatment (29,6%). The nonadherent/non-compliant group showed statistically the same demographic, clinic, and polysomnographic characteristics when compared to the compliant group. The level of maximum pressure during the titration test was lower in the compliant group (p=0,040). Conclusion: The sleep-related symptoms, scores of ESS or polysomnographic parameters can not be used to predict compliance for mild OSAS. The patients with mild OSAS, especially the ones who reach higher maximum pressure on titration test, must be followed up closely during the first 2 months of PAP treatment to detect nonadherence/non-compliance earlier.